2017
DOI: 10.1016/j.ajur.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and benign prostatic hyperplasia: An update

Abstract: Metabolic syndrome (MetS) is a cluster of metabolic abnormalities related to central adiposity and insulin resistance. Its importance is increasingly recognized as it associates with increased risks of metabolic and cardiovascular diseases. These metabolic aberrations of MetS may lead to development of benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS) in men. A 26.5%–55.6% prevalence of MetS in men with LUTS was reported in worldwide studies. Although the exact biological pathway is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 107 publications
(126 reference statements)
1
34
0
3
Order By: Relevance
“…A re‐consideration of some of the aetiological factors may help shed light on the need to re‐examine some old and new biomarkers. Metabolic syndrome (MetS) is a common feature of the two conditions (Gacci et al, ; Ngai, Yuen, Ng, Cheng, & Chu, ). The role of lipids in the pathogenesis of BPH and PCa is also an established fact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A re‐consideration of some of the aetiological factors may help shed light on the need to re‐examine some old and new biomarkers. Metabolic syndrome (MetS) is a common feature of the two conditions (Gacci et al, ; Ngai, Yuen, Ng, Cheng, & Chu, ). The role of lipids in the pathogenesis of BPH and PCa is also an established fact.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome itself is made up of various factors such as visceral adiposity, dyslipidaemia, endothelial dysfunction and insulin resistance (Kaur, ). These metabolic abnormalities may then promote the development of BPH and LUTS (Ngai et al, ). Furthermore, accumulation and faster synthesis of cholesterol in prostate cells compared to the liver have been demonstrated (Krycer & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…For macronutrients, increased total energy intake, energy-adjusted total protein intake, red meat, fat, milk and dairy products, cereals, bread, poultry and starch potentially increase the risks of symptomatic BPH, while vegetables (particularly carotenoids), fruits, polyunsaturated fatty acids, linoleic acid, lutein, Vitamin C, Vitamin A and Vitamin D potentially decrease the risks of symptomatic BPH and LUTS. [25][26][27] Based on the studies reviewed, a holistic framework has been suggested in ►Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current standard pharmacotherapy of PA is often not effective enough for a number of patients, especially those with systemic hormonal and metabolic disorders (obesity, insulin resistance, testosterone deficiency, vitamin D deficiency), which tends to increase in frequency in the male population and significantly reliably correlate with one another, as well as with the frequency and severity of PA (Park et al 2008;Gorbachinsky et al 2010;Vignozzi et al 2012;Espinosa 2013;Tyuzikov and Kalinichenko 2016;Udensi and Tchounwou 2016;Wang et al 2016;Zou et al 2016;Ngai et al 2017).…”
Section: Introductionmentioning
confidence: 99%